Identification of Trap States in p-GaN Layer of a p-GaN/AlGaN/GaN Power HEMT Structure by Deep-Level Transient Spectroscopy - Yang, Song; Huang, Sen; Wei, Jin; Zheng, Zheyang; Wang, Yuru; He, Jiabei; Chen, Kevin J. (IEEE electron device letters, 2020)
In this work, the deep-level transient spectroscopy (DLTS) is conducted to investigate the gate stack of the {p} -GaN gate HEMT with Schottky gate contact. A metal/ {p} -GaN/AlGaN/GaN heterojunction capacitor is prepared for the study. The DLTS characterization captures the transient capacitance change in the stack, from which the capacitance of the metal/ {p} -GaN Schottky junction can be extracted. By proper selection of the rate window, the impacts of the hole insufficiency effect are avoided during trap states evaluation. Thus, the information of deep energy levels in the {p} -GaN layer is revealed, which consists of an electron trap state with activation energy of 0.85 eV and a hole trap state with activation energy of 0.49 eV. The identification of these trap states in the {p} -GaN layer provides a physical foundation for understanding the threshold voltage instability in Schottky-type {p} -GaN gate power HEMTs.